Temperature Effect Study on Growth and Survival of Pathogenic Vibrio parahaemolyticus in Jinjiang Oyster (Crassostrea rivularis) with Rapid Count Method - Yuan Wang; Hai-yan Zhang; Essy Kouadio Fodjo; Cong Kong; Run-Run Gu; Feng Han; Xiao-Sheng Shen (Journal of Food Quality)
The growth of Vibrio parahaemolyticus (V. parahaemolyticus) in oysters during postharvest storage increases the possibility of its infection in humans. In this work, to investigate the growth or survival profiles in different media, pathogenic V. parahaemolyticus in APW, Jinjiang oyster (JO, Crassostrea rivularis) slurry, and live JO were studied under different temperatures. All the strain populations were counted through our double-layer agar plate (DLAP) method. In APW, the pathogenic V. parahaemolyticus showed continuous growth under 15, 25, and 35°C, while a decline in behavior was displayed under 5°C. The similar survival trend of pathogenic V. parahaemolyticus in JO slurry and live JO was observed under 5, 25, and 35°C, except the delayed growth or decline profile compared to APW. Under 15°C, they displayed decline and growth profile in JO slurry and live JO, respectively. These results indicate the different sensitivity of pathogenic V. parahaemolyticus in these matrices to temperature variation. Furthermore, nonpathogenic V. parahaemolyticus displayed little difference in survival profiles when inoculated in live JO under corresponding temperatures. The results indicate that inhibition or promotion effect could be regulated under different storage temperature for both pathogenic and nonpathogenic strains. Besides, the DLAP method showed the obvious quickness and efficiency during the bacteria count.